CONTENT CONTROL MANAGEMENT IN OIL WATER SEPARATOR WASTE WATER - Lantang, Dianita Veronica (Indonesian Journal Of Maritime Review, 2023)
Maritime world Oil Water Separator (OWS) adalah pesawat yang mampu memisahkan air dari air buangan yang mengandung minyak sampai hasil pemisahannya mencapai kurang dari 15 ppm. Tujuan dari penelitian ini yakni untuk mengetahui penyebab oil water separator tidak dapat bekerja dengan maksimal, dampak dari kandungan minyak pada air buangan oil water separator lebih dari 15 PPM serta upaya mengatasi kandungan minyak pada air buangan Oil Water Separator lebih dari 15 PPM di kapal Yong Xing Shun Hang. Penelitian ini merupakan penelitian kualitatif ekploratif. Based on the discussion in the previous chapter, the author can draw conclusions, namely the factors causing the high oil content in wastewater resulting from the Oil water separator process, namely the implementation of maintenance schedules are not on time, dirty coalesscer filters, bilge well contains a lot of dirt. The impact caused by factors that cause high oil content in wastewater from the oil water separator process consists of the impact caused by the implementation of the maintenance schedule is not on time is the hampering of the operation of the oil water separator, sudden damage to the oil water separator components, less than optimal performance of the oil water separator And the impact caused by dirty coalesscer filters is less than optimal filtering of dirt / filtering process